Report of the External Evaluation of the Independent Evaluation Office. (Policy Papers; Policy Paper ;, 2006)
The IEO of the IMF was created in 2000 to enhance the learning culture of the IMF, to build the IMF's external credibility by undertaking objective evaluations in a transparent manner, to provide independent feedback to the Executive Board in its governance and oversight responsibilities, and to promote greater understanding of the work of the IMF among its members and the broader public. In the period October 2005-February 2006, the Evaluation Panel assessed how well the IEO meets these objectives, asking at the outset whether the IMF needs an IEO and whether the existing office is adequately independent. The Panel concludes that the IEO has served the IMF well but identifies certain weaknesses and makes recommendations to the IEO and the IMF to address them.